2019
DOI: 10.1080/09712119.2019.1598420
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of velogenic viscerotropic Newcastle disease virus infection were more severe in broilers than pullets

Abstract: velogenic viscerotropic Newcastle disease virus infection were more severe in broilers than pullets,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…All challenged groups showed diffuse necrotic nephritis which involved the renal tubules [ 51 , 72 , 73 , 74 ], while the choanal group showed focal renal necrotic lesions, suggesting a wider systemic distribution of NDV through other routes of inoculation [ 62 ]. In terms of the lymphoid organs (bursa of Fabricius, spleen, thymus, and cecal tonsils), several lesions were noticed in all inoculated groups, including lymphocytic depletion and necrosis, in agreement with several previous reports [ 55 , 61 , 74 , 75 ]. The observed lymphoid depletion might be attributed to the multiplication of the virus and its presence in lymphocytes, which consequently greatly reduced the immune status of the birds [ 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…All challenged groups showed diffuse necrotic nephritis which involved the renal tubules [ 51 , 72 , 73 , 74 ], while the choanal group showed focal renal necrotic lesions, suggesting a wider systemic distribution of NDV through other routes of inoculation [ 62 ]. In terms of the lymphoid organs (bursa of Fabricius, spleen, thymus, and cecal tonsils), several lesions were noticed in all inoculated groups, including lymphocytic depletion and necrosis, in agreement with several previous reports [ 55 , 61 , 74 , 75 ]. The observed lymphoid depletion might be attributed to the multiplication of the virus and its presence in lymphocytes, which consequently greatly reduced the immune status of the birds [ 76 ].…”
Section: Discussionsupporting
confidence: 92%
“…These lesions agree with overt clinical signs reported by poultry handlers such as difficulty in breathing, greenish diarrhoea, weakness, and anorexia with wing and leg paralysis as the most common neurological symptoms among flocks. Haemorrhage at the tip of the proventriculus is highly suggestive of ND [ 26 , 27 ]. Generally, distributed lesions suggest that the virus is able to infect and replicate in most organs, typical of vNDV as supported by the cleavage site motif of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study identified a significant difference in the severity of tissue (proventriculus, intestinal, and cecal tonsil) lesions in 10-week-old chickens (broilers and pullets) that were infected with velogenic NDV, with very severe lesions observed in broilers compared to pullets [ 20 ]. The differences in NDV susceptibility between breeds or ecotypes might explain differences in clinical signs and mortality between Ghana and Tanzania local chicken ecotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Selection for increased survival time could reduce gastro-intestinal tract (GIT) lesion development, which may enable birds to ultimately fight off velogenic NDV. A previous study indicated that NDV infection caused more mortalities and higher lesion scores in broilers than in pullets [ 20 ]. In chickens, high GIT lesion infestation is often attributed to hemorrhages and ulcers, and this can significantly increase the severity of NDV infection in chickens compared to other poultry species [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation